Mensuração do grau de maturidade da governança corporativa em cooperativas de crédito pelo método Análise Hierárquica de Processos - AHP - Paiva, Benedito Geovani Martins de (2018)
The main objective of this research was to structure a model to measure the level of maturity of corporate governance in credit cooperatives and to delineate the profile of this market located in the South of Minas Gerais. Two central questions guided this research: 1. Is it possible to develop a methodology through a set of indicators to measure the maturity of Governance in Credit Cooperatives? 2. What are the most frequent variables that can interfere in the maturity of governance in Credit Cooperatives? The theoretical approach was based on corporate governance and credit cooperatives, as an object of study. The research defined a methodology to measure the maturity of corporate governance in credit cooperatives, using the AHP Method, developed by Saaty (1991), based on the IBGC's Guide to Best Practices for Governance for Cooperatives. The developed index was called the Corporate Governance Maturity Index for Credit Cooperatives - CGMIcc. This methodology was applied in the corpus of the research, which included 26 loan cooperatives from the South of Minas Gerais. As for the methodological procedures, the quantitative approach was adopted with the objective of knowing the degree of maturity of corporate governance in the credit cooperatives under study. Based on the research, it was evidenced, with regard to the maturity of corporate governance, that credit cooperatives predominate with IMGCcc 5, in the total of 11, (40.74%); with IMGCcc 4 in total of 6, (22.22%); with IMGCcc 3 in total of 5 (18.52%) and with IMGCcc 2 in the total of 4, (14.81%). This advanced maturity can be explained by the predominance of the Free Admission association and the legal requirements of the adoption of corporate governance practices. Regarding the variables that may interfere with the IMGCcc, there was a high correlation with Revenue (R = 0.8256 and R² = 0.6816), Shareholders' Equity (R = 0.7141 and R² = 0.5041) and Total Asset (R = 0.8060 and R² = 0.6496), indicating that cooperatives with a higher volume of Revenues, Shareholders' Equity and Total Assets tend to have higher IMGC rates. As for the contributions, the main and original, for the academy, was the creation of a maturity index of corporate governance for credit unions, using the AHP Method, the second was the diagnosis of maturity of corporate governance in credit unions. credits from the South of Minas Gerais and the third was the correlation between the Revenue, Equity and Total Assets and the maturity of corporate governance in credit cooperatives